Evaluation of Fresh Semen Quality and Frozen Semen Production for Candidate Bulls Progeny Test at Singosari National Artificial Insemination Center - Andila, Rizkhy Ervanda; Atabany, Afton; Purwanto, Bagus Priyo (Universitas Halu Oleo, 2023)
The progeny test activity aims to improve genetic quality and produce proven bulls for dairy cows. Evaluation of semen quality is one approach to determining bull fertility. This research determines the best candidate bull (CB) for the progeny test at National Artificial Insemination Center (NAIC) Singosari based on the quality of fresh semen and frozen semen production. The material used secondary data from the third period of the progeny test of three candidate bulls, namely Shoty, Doming, and Glens, from 2016 to 2020. Data were analyzed using descriptive analysis. The results showed that the volume, pH, mass movement, individual motility, and sperm concentration of Shoty, Doming, and Glen's fresh semen were 6.16±1.87; 7.61±1.89 and 7.68±1.86 mL, 6.50±0.17; 6.48±0.16 and 6.40±0.16, 2.21±0.41; 2.28±0.45 and 2.28±0.45, 72.43±0.05; 73.86±0.06 and 74.07±0.07%, and 938.80±287.90; 953.24±266.52 and 1144.72 ±307.47 106/mL. Frozen semen production of Shoty, Doming, and Glens were 234.68±108.00, 294.80±114.76, and 357.25±146.29 straws. In conclusion, the quality of fresh semen and frozen semen production of the three candidate bulls was relatively high, and the best CB is Glens, followed by Doming and Shoty. Keywords: progeny test, candidate bull, fresh semen quality, frozen semen production